2022
DOI: 10.1002/mnfr.202100863
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A Attenuates Diabetes‐Associated Cognitive Impairment by Ameliorating Intestinal Barrier Dysfunction via N‐glycan Biosynthesis Pathway

Abstract: Scope This study aims to investigate the effect of Urolithin A (UA) on diabetes‐associated cognitive impairment in type 2 diabetes mellitus (T2DM) mouse model induced by high‐fat diet (HFD) and streptozotocin (STZ). Methods and Results The UA‐treated T2DM mice display an attenuated cognitive impairment as well as reduced levels of metabolic endotoxemia and proinflammatory cytokines in serum. A systemic restraint of gut/brain inflammation in UA‐treated T2DM mice is also observed as the downregulation of TLR4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Cani et al, 2009;Li et al, 2019). Our detection results of intestinal barrier integrity related parameters showed that the intestinal barrier integrity was damaged in DCI mice, which was consistent with previous reports (Visser et al, 2010;Li et al, 2022;Xiao et al, 2022). Likewise, our results show that ZSWF exhibits a protective effect on intestinal barrier integrity in DCI mice by increasing colon tight junction protein expression (ZO-1 and occludin) and mucin (Muc2) content, as well as colon content immunoglobulin A (SlgA) levels.…”
Section: Discussionsupporting
confidence: 92%
“…Cani et al, 2009;Li et al, 2019). Our detection results of intestinal barrier integrity related parameters showed that the intestinal barrier integrity was damaged in DCI mice, which was consistent with previous reports (Visser et al, 2010;Li et al, 2022;Xiao et al, 2022). Likewise, our results show that ZSWF exhibits a protective effect on intestinal barrier integrity in DCI mice by increasing colon tight junction protein expression (ZO-1 and occludin) and mucin (Muc2) content, as well as colon content immunoglobulin A (SlgA) levels.…”
Section: Discussionsupporting
confidence: 92%
“…UroA is a gut microbiome-derived metabolite of dietary ellagitannins belonging to the family of urolithins characterized by a chemical structure containing the α-benzo-coumarin scaffold that shows health benefits for metabolic diseases and age-related conditions. Previous studies have demonstrated the protective role of UroA against metabolic dysfunctions in vivo , such as atherosclerosis, metabolic cardiomyopathy, and obesity. Relevant data concerning the regulation of glucose metabolism have demonstrated that UroA ameliorated hyperglycemia, insulin resistance, and glucose intolerance in diet-induced-obesity mice. , Also, UroA robustly lowered fasting blood glucose in a diet-induced insulin resistance mouse model by inhibiting hepatic gluconeogenesis . Moreover, UroA could reduce fasting blood glucose, after-glucose-loading glucose, and glycated hemoglobin levels by restoring pancreatic β cell function via autophagy activation in a type 2 diabetes model induced by HFD and streptozotocin injection .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are many studies on the ameliorative effect of Uro A on DM and its complications, and most of them are mainly achieved by improving insulin resistance [112,113]. However, the effects and mechanisms of Uro A directly acting on β cells to boost glucose metabolism disorders were not discussed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Albasher et al further demonstrated that Uro A prevents streptozotocin (STZ)-induced DCM in rats by activating SIRT1 expression and deacetylase activity [112]. Xiao et al suggested that Uro A can attenuate DM-related cognitive impairment by ameliorating systemic inflammation and intestinal barrier dysfunction through the N-glycan biosynthesis pathway [113]. This conclusion was also supported by Lee et al They pointed out that Uro A prevented DM-associated AD by reducing transglutaminase type 2 (TGM2)-dependent mitochondria-associated ER membrane (MAM) formation and maintaining mitochondrial calcium and ROS homeostasis [35].…”
Section: Protects Pancreatic β Cellsmentioning
confidence: 99%